The implications of transfrontier conservation areas : a comparative policy analysis study of sustainable development in South Africa between the great Limpopo transfrontier conservation area and Lubombo transfrontier resource area - Herholdt, A.N.J. (University of Pretoria, 2013)
Dissertation (MA(Political science))--University of Pretoria, 2007.